Wood Anatomical Features and Physical Properties of Fast Growing Red Meranti from Line Planting at Natural Forest of Central Kalimantan - Joko Sulistyo; Harry Praptoyo; Ganis Lukmandaru; Ragil Widyorini; Widyatno Widyatno; Oka Karyanto; Sri Nugroho Marsoem (Wood Research Journal, 2018)
High productivity fast growing species plantation establishment such as the line planting of red meranti (i.e Shorealeprosula and Shorea parvifolia) with intensive silviculture is one potential solution to improve wood supply for industries in Indonesia. However, the information of anatomical properties and wood properties of these two species related to the influence of the line planting system and tree growth rate is limited. This paper studies the anatomical features, wood cell proportions, fiber dimensions and physical properties of wood in radial variation in relation to the line planting effect and tree growth rate. Wood of the trees grown in the line planting system showed higher proportion of vessel element compared to those of wood from natural forest. The vessel diameter of wood from the line planting was also larger than that of in wood from natural forest. The specific gravity of wood from Shorea parvifolia grown on the line planting was higher than that of wood grown in natural forest. The variation of specific gravity on wood portion near to the pith of Shorea leprosula and Shorea parvifolia trees grown on the line planting was related to the variation of the cell wall thickness. The bigger diameter of trees grown or the faster growth rate in the line of planting at the same age shows the greater vessel diameter in wood of Shorea leprosula and Shorea parvifolia and greater specific gravity of Shorea parvifolia wood.